Import Competition and Skill Content in U.S. Manufacturing Industries - Lu, Yi; Ng, Travis (The Review of Economics and Statistics, 2013)
Skill content varies enormously across industries and over time. This paper shows that import competition can explain a significant portion of the variation in various skill measures across manufacturing industries. Industries that face more intense import competition employ more nonroutine skill sets, including cognitive, interpersonal, and manual skills, and fewer cognitive routine skills. In addition, we find that the impact of import competition on skills is not driven by imports from low-wage countries or from China. A number of robustness checks also suggest that our results are unlikely to be driven by econometric problems.